The “normal” normal: Supply and demand drivers over the next 10 years - Meyer, Seth; Glauber, Joseph W. (Federal Reserve Bank of Kansas City, 2019)
From 2010 to 2015, farmers saw the longest period of sustained above-average farm income since World War II and its immediate aftermath (Chart 1). In the United States, real net cash and net farm income were above their 1960–2017 average for six consecutive years. By contrast, real net cash and net farm income were only above the 1960–2017 average for four consecutive years in the 1970s (from 1972 to 1975). The run-up in prices in the early 1970s—and the associated brief jump in farm income—originated in oil price shocks and inflationary pressure that set the stage for economic turmoil in the agricultural sector in the first half of the 1980s. The recent period of strong farm income was similarly driven by a surge in producers’ crop and livestock prices. As food prices began to rise in 2007 and 2008 and peaked in 2011, U.S. corn, soybean, and wheat prices all hit record nominal prices for the 2012–13 crop year.